The Functioning of the Natura 2000 Areas Situated in National and Landscape Parks - Gotkiewicz, Wojciech (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2010)
The article presents the results of research carried out in 2009 in three national and seven landscape parks situated on the territory of the Green Lungs of Poland region. During empirical studies a questionnaire prepared for the purpose of conducting interviews was used. Investigations covered a very important and topical problem of the functioning of the Natura 2000 areas within the boundaries of national and landscape parks. An analysis was conducted of the remarks and opinions offered by the parks’ workers on the subject of co-existence of the earlier described forms of protection of the natural environment, of socio-economic conflicts and their resolution in the areas managed by them, and effectiveness of current legal instruments serving environmental protection.
Keywords: Natura 2000; national parks; landscape parks